A Study on the Socio demographic Profile of the Attendees at the Integrated Counseling and Testing Centre of Institute of Medical Sciences BHU, Varanasi, Uttar Pradesh - Kumari, Rashmi; Kumar, Mritunjay; Gulati, A K; Sundar, Shyam; Mohapatra, S C (Indian Journal of Community Health, 2016)
Introduction: Human Immunodeficiency Virus (HIV) counseling and testing services are a key entry point to the prevention of HIV infection and to the treatment and care of the people who are infected with HIV. The Integrated Counseling and Testing Centre (ICTC) services are a cost effective intervention in the prevention of HIV/AIDS. Aims: To study the socio demographic characteristics of the attendees at the ICTC centre. Material and Methods: Setting – ICTC of Institutes of Medical Sciences BHU, Varanasi, Study Design: A cross-sectional, record based study, Study duration: The study population included 41159 clients who attended the ICTC centres from January 2009 to December 2011. Results: An overall 12.85% of the ICTC attendees were HIV Seropositive subjects. During 2009 to 2011. i.e. during past 3 years total males tested for HIV at the ICTC were 23326, out of which 3202 were HIV+ve showing positivity rate of 13.7%, while total females tested were 16671 out of which 2063 were HIV+ve showing positivity rate of about 12.4%. Consecutively in the last three years maximum load of patients was from the age groups 35-49 years (19.13%) followed by 25-34 years (15.4%). Conclusion: People’s attitudes towards HIV are changing after the introduction of the ICTC, which plays a major role in the primary and secondary prevention of HIV. There is a more urgent need for the introduction of interventional measures like sex education and preventive education among the general population